Thin Film for Q-Switching Application in Erbium-Doped Fiber Laser - Mahmoud. M. Ahmeed,; L. S. Supian,; D. A. Zainal,; Khadijah Ismail,; S. W. Harun,; A. R. Abdul Rahman, (Fakulti Kejuruteraan ,UKM,Bangi., 2025)
This study demonstrates the utilization of a Scandium Oxide (Sc2O3 ) film as a passive saturable absorber (SA) for pulse generation within the C-band region in an Erbium-Doped Fiber Laser (EDFL) cavity for possible applications in metrology, sensing, and medical diagnostics. The SA was fabricated using Sc2O3 powder, with polyvinyl alcohol (PVA) employed to form the film. The experimental setup utilized an all-fiber ring cavity configuration. Q-switching was achieved over a range of pump powers from 48.8 mW to 84.8 mW. It is observed that as the pump power increased, the repetition rate rose from 42.3kHz to 82.8 kHz, accompanied by a reduction in pulse width from 5.04 μs to 2.82 μs. At a pump power of 84.8 mW, the system achieved a maximum output power of 6.75 mW and a maximum pulse energy of 81.6 nJ. The EDFL also has a high signal-to-noise ratio (SNR) at the fundamental frequency which is 55.4 dB, highlighting the stability of the Q-switched pulses.